Research on the spatial perception and preferences of traditional villages from the perspective of local gaze: a case study of Hongkeng Village, China (EAAE Annual Conference Proceedings, 2023)
As one of the World Cultural Heritage Sites, Hongkeng Village in China is a typical representative of the traditional Hakka villages. With the advent of the era of mass tourism, it is important to understand the perception, preference and identity of local people towards the village space from the perspective of local gaze, in order to maintain the characteristics of the village and perpetuate its vitality.